208k views
4 votes
Find A-
2x + y + 3z = 6
3x + 2y + z = 6
x + 3y + 2z = 6

User Bince
by
4.8k points

1 Answer

2 votes

Answer:

x = 1

y = 1

z = 1

Explanation:

You could use Cramer's rule, with matrices.

First to find the determinent,

We get 8 + 1 + 27 - 6 - 6 -6. or 18.

Since the determinant is a non-0 number, we know there is an answer to this problem.

Then we can solve for X.

We get 24 + 6 + 54 - 36 - 18 - 12, or 18.

So x = 18/18, or 1.

Next to solve for Y:

We get 24 + 6 + 54 - 18 - 12 - 36, or 18. So y = 18/18 or 1.

Next we can plu in the values we already have for x an y and solve for xz So, 2(1) + 2 + 3z = 6

So Z = 1

Then we finally have all our answers x = 1, y = 1, and z = 1

Find A- 2x + y + 3z = 6 3x + 2y + z = 6 x + 3y + 2z = 6-example-1
User Steven Lu
by
5.1k points